PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK BERBASIS QUICK RESPONSE (QR) CODE PADA PELAJARAN AKIDAH AKHLAK - Putri Apriliani; Jaelani, Aceng; Binasdevi, Misbah (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2024)
The background of this research is that the learning process in class III shows that using conventional media alone makes learning less interesting and less enjoyable. The aim of this research is to develop Quick Response (QR) Code-based comic learning media for moral belief lessons, determine the level of appropriateness of the media developed, and analyze user responses to the development of Quick Response (QR) Code-based comic learning media. The research method used is a research and development method using the ADDIE development model involving the Analysis, Design, Development, Implementation and Evaluation stages. Material expert validation feasibility test, the score obtained was 65, so the feasibility percentage obtained was 93%, which is included in the criteria for very valid or very suitable for use. The media expert validation feasibility test was carried out twice. In the first validation, the score obtained was 90, so the feasibility percentage obtained was 90%, including the criteria for very valid or very suitable for use. The linguist validation feasibility test, the score obtained was 33, so the feasibility percentage obtained was 94%, which is included in the criteria for very valid or very suitable for use. The results of student responses obtained a score of 44.63 or a percentage of satisfaction with use, namely 89.26%. So the satisfaction of using QR Code-based comic learning media is in the very satisfying category.